Intuitive fasting : the flexible four-week intermittent fasting plan to recharge your metabolism and renew your health - Cole, Will (Functional medicine expert) (Goop Press, Rodale, 2021)
"The most effective and achievable guide to intermittent fasting, outlining a unique plan that merges the science behind fasting with a holistic approach to eating, from the bestselling author of Ketotarian and The Inflammation Spectrum"--